KONSEPTUALISASI KERANGKA KERJA ANALISIS KETAHANAN TIM PADA PROYEK PENGEMBANGAN PRODUK BARU DI INDUSTRI OTOMOTIF - Nurizzati, Annisa; Permatasari, Intan; Khairiyah, Amirah Nova (Industry Xplore, 2025)
Quality scandals in the automotive industry have had a significant impact on new product development projects. This study examines the concept of team resilience in new product development projects within the automotive industry as a response to the effects of quality scandals. Based on the notion that every project must be prepared to face threats, whether anticipated or unexpected, the concept of resilience emerges as a solution to help organizations survive and recover from setbacks. Although new product development projects in the automotive industry are project-based organizations, studies on team resilience remain limited. Therefore, this research aims to develop a conceptual framework for team resilience applicable to new product development projects in the automotive industry. The framework is based on the latest team resilience theories and is modified by integrating relevant contextual factors, thereby facilitating the empirical testing of key variables at both the individual and project levels. Variables were selected through a review of previous empirical studies that highlighted dominant variables and adjusted to reflect real-world conditions. This study is expected to contribute significantly to understanding the implementation of team resilience and to support project success. It also opens opportunities for innovative strategies to significantly enhance competitiveness in the automotive sector.